2020
DOI: 10.3390/su12187303
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainability Assessment of the Greenseeker N Management Tool: A Lysimetric Experiment on Barley

Abstract: A preliminary study was conducted to analyze the sustainability of barley production through: (i) investigating sensor-based nitrogen (N) application on barley performance, compared with conventional N management (CT); (ii) assessing the potential of the Normalized Difference Vegetation Index (NDVI) at different growth stages for within-season predictions of crop parameters; and (iii) evaluating sensor-based fertilization benefits in the form of greenhouse gasses mitigation. Barley was grown under CT, sensor-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…Colaco et al (2018) [66] observed that using sensor-based technology for identifying the period of maximum crop demand, yields increased by 17% compared to conventional methods. This is in accordance with our previous study [67] in which we observed that performing fertilization at the right growing stage allows a reduction of 50% in the N rate while maintaining high yields of barley. The relevance of the rational use of fertilizers was highlighted by [68] who observed that on reducing the N rate on sweet potato by 20%, yields increased by 16.6-19% compared to conventional doses.…”
Section: Crop Yield and N Content Under Different Fertilizer Sources ...supporting
confidence: 93%
“…Colaco et al (2018) [66] observed that using sensor-based technology for identifying the period of maximum crop demand, yields increased by 17% compared to conventional methods. This is in accordance with our previous study [67] in which we observed that performing fertilization at the right growing stage allows a reduction of 50% in the N rate while maintaining high yields of barley. The relevance of the rational use of fertilizers was highlighted by [68] who observed that on reducing the N rate on sweet potato by 20%, yields increased by 16.6-19% compared to conventional doses.…”
Section: Crop Yield and N Content Under Different Fertilizer Sources ...supporting
confidence: 93%
“…Pani Modied Ag NP 46 Fluorescent 0-14 mM 8.9 × 10 −4 M Nitrate detection in crop Crop Circle [47][48][49] Reflectance Not specified Not specified Remote sensing tool, Nutrient and fertilizer studies GreenSeekerTM 50,51 Reflectance Not specified Not specified Handheld, targeted nutrient management decisions FieldScout [52][53][54] Reflectance Not specified Not specified Handheld, Nutrient mapping SPAD-502 21,24,[55][56][57] Chlorophyll 0-80 SPAD units Not specified Non-destructive measurement of leaf chlorophyll concentrations atLeaf CHL Plus 58,59 Chlorophyll 0-60 SPAD units Not specified Assessing and improving plant N management Low-cost chlorophyll meter 57 Chlorophyll Not specified Not specified Self-cultivation, small-scale farming, and crop research…”
Section: Nitrate Detection In Aqueous Mediummentioning
confidence: 99%
“…Thus, a real time N management strategy offering higher N use efficiency and net N saving reduces the threat of global warming. Moreover, precision N management by using optical crop sensor matches with the crop N demand both spatially and temporally, thus increases N use efficiency and mitigate negative environmental impacts [25].…”
Section: Optical Crop Sensor Based N Use and Global Warming Potentialmentioning
confidence: 99%